2014
DOI: 10.1177/0011000014542599
|View full text |Cite
|
Sign up to set email alerts
|

Training Undergraduate Students to Use Challenges

Abstract: After they learned exploration skills, 103 undergraduate helping skills students were taught to use challenges. Prior to training, students' selfefficacy for using challenges did not change, although the quality of written challenges and reflections of feelings did. After training, students rated themselves as having more self-efficacy for using challenges and were judged as providing better written challenges, although there were no further changes in quality of written reflections of feelings. Students maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 6 publications
3
41
0
1
Order By: Relevance
“…Although this study was similar in purpose and format to the and Chui et al (2014) studies of training for the use of immediacy and challenge, there were a few important differences based on trainee feedback from the previous studies. We designed a standardized lecture that covered the crucial points in the text but also included new information on developing and delivering interpretations when working with clients.…”
Section: Purposes Of the Present Studymentioning
confidence: 99%
“…Although this study was similar in purpose and format to the and Chui et al (2014) studies of training for the use of immediacy and challenge, there were a few important differences based on trainee feedback from the previous studies. We designed a standardized lecture that covered the crucial points in the text but also included new information on developing and delivering interpretations when working with clients.…”
Section: Purposes Of the Present Studymentioning
confidence: 99%
“…The effect sizes for the changes across the delay condition were 0.06 for Spangler et al (2014) and 0.21 for Jackson et al (2014). In the Chui et al (2014) study, no changes were found for students from the beginning of the semester to right before training in challenges (d = 0.10). These data provide compelling evidence that students did not gain self-efficacy during the period of time prior to training in the target skill.…”
Section: Comparison Of Samplesmentioning
confidence: 76%
“…These results suggest that students were initially least confident in their ability to use immediacy as compared with challenges or interpretation, perhaps because immediacy felt less familiar prior to training. In terms of final levels of self-efficacy, participants in the Chui et al (2014) study were higher at post training than those in the Spangler et al (2014) or Jackson et al (2014) studies (ds = 0.62 and 0.45, respectively), with no differences between the latter two studies. These results suggest that students felt the most confident after training in their ability to use challenges, perhaps because challenges are easier to learn.…”
Section: Comparison Of Samplesmentioning
confidence: 80%
See 1 more Smart Citation
“…Chui et al, 2014;Goates-Jones, 2004;Goates-Jones et al, 2009;Hill, 2005;Hill et al, 2015;Jackson et al, 2014;Meystre et al, 2014;Spangler et al, 2014). The HSS codes several types of therapist interventions, organized around three major categories: i) exploration skills (related to an exploration phase of psychotherapy, aim to deepen the exploration of client problems, through the use of approval and reassurance, closed questions, open questions, restatements and reflections of feelings); ii) insight skills (related to an insight phase of psychotherapy, aim to facilitate increased client insight regarding difficulties, through the use of challenges, interpretations, disclosures and immediacy); and iii) action skills (related to an action phase of psychotherapy, aim to help clients transform their lives through new actions or behaviors, through information and direct guidance -Hill, 2014).…”
Section: The Present Study: Therapist's Interventions and Client's Immentioning
confidence: 99%